2016
DOI: 10.1002/anie.201608924
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Polymer/Garnet Electrolyte with a Small Interfacial Resistance for Lithium‐Ion Batteries

Abstract: Li La Zr O -based Li-rich garnets react with water and carbon dioxide in air to form a Li-ion insulating Li CO layer on the surface of the garnet particles, which results in a large interfacial resistance for Li-ion transfer. Here, we introduce LiF to garnet Li La Zr Ta O (LLZT) to increase the stability of the garnet electrolyte against moist air; the garnet LLZT-2 wt % LiF (LLZT-2LiF) has less Li CO on the surface and shows a small interfacial resistance with Li metal, a solid polymer electrolyte, and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
311
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(324 citation statements)
references
References 34 publications
2
311
0
Order By: Relevance
“…Li ions migrate between cathodes and anodes through electrolytes and separators repeatedly to experience the electrochemical reactions in rechargeable batteries ( 24 , 25 ). Because of the ionically insulated nature of the commercial separator skeleton, the electrolytes in the separators pave the way for Li-ion transport between cathodes and anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Li ions migrate between cathodes and anodes through electrolytes and separators repeatedly to experience the electrochemical reactions in rechargeable batteries ( 24 , 25 ). Because of the ionically insulated nature of the commercial separator skeleton, the electrolytes in the separators pave the way for Li-ion transport between cathodes and anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of impurity phases such as LiOH and Li 2 CO 3 , and weak physical adhesion of two phases have been considered as the main origin of high interfacial resistance. 9,10 Park et al have shown that cubic garnet structure changes to tetragonal phase with lower ionic conductivity, this phenomenon intensified when the LiCoO 2 was directly formed on the LLZO substrate. They have also shown that annealing time intensifies reaction between these * Electrochemical Society Student Member.…”
mentioning
confidence: 99%
“…The developed polymer-based SSEs demonstrated high ionic conductivity and good accommodation with Li metal anode which breaks the bottleneck that allow the polymer-based ASS Li-S batteries operating at ambient temperature. Many groups have attempted to develop hybrid electrolytes with the combination of polymer and oxide-based electrolytes, which demonstrated enhanced stability and conductivity [411][412][413][414][415]. Despite the excellent electrochemical performance, the loading of these sulfur and Li 2 S-based cathodes are unsatisfactory and unsuitable for commercial application.…”
Section: Polymer Electrolyte-based Li-s Batteriesmentioning
confidence: 99%